Correlation between estimated glomerular filtration rate and serum electrolytes in chronic kidney disease patients - Ramkrishna Nagar,; Dinesh Kumar Malviya,; Manoj Indurkar, (Asian Journal of Medical Sciences, 2023)
Background: The occurrence of chronic kidney disease (CKD) a highly prevalent condition has been escalating in recent years. Electrolytes are the key to homeostasis and furthermore, their regulation is dependent upon renal function. CKD is associated with aberrations in the metabolism of electrolytes such as calcium, magnesium, sodium, and potassium. Aims and Objectives: The aim of this study is to study the correlation between estimated glomerular filtration rate (eGFR) and serum electrolytes in CKD patients. Materials and Methods: The present study was a cross-sectional study. One hundred patients with CKD aged 18 years or above were enrolled with inclusion and exclusion criteria. Complete blood investigations, urine analysis and ultrasonographic findings for detection of CKD were done and a semi-structured pro forma was used to record clinical profile in a cross-sectional study and patients were grouped into their respective CKD stages based on their eGFR. Results: The mean value of eGFR was 40.92±21.35 mL/min/1.73 m2. The mean value of serum sodium, calcium, magnesium, and potassium was 137.1±2.16 meq/L, 9.15±0.61 mg/dL, 3.16±0.93 mg/dL, and 4.65±0.96 meq/L, respectively. In the present study, we found that the mean serum magnesium levels in Stages 1, 2, 3, 4, and 5 of CKD were 2.10±0.20, 2.10±0.28, 2.74±0.50, 3.95±0.54, and 4.66±0.43 mg/dL, respectively. Mean serum magnesium levels were the mean serum potassium levels in Stages 1, 2, 3, 4, and 5 of CKD were 4.13±0.57, 4.15±0.68, 3.86±0.41, 5.55±0.39, and 6.25±0.08 meq/L, respectively. The mean serum calcium levels in Stages 1, 2, 3, 4, and 5 of CKD were 9.83±0.05, 9.79±0.20, 9.43±0.27, 8.72±0.38, and 7.8±0.10 mg/dL, respectively. The mean serum sodium levels in Stages 1, 2, 3, 4, and 5 of CKD were 137.33±0.57, 136.43±2.87, 136.92±2.15, 137.51±1.90, and 137.5±2.07 meq/L, respectively. Conclusion: There was significant rise in serum potassium and magnesium levels with decrease in eGFR in CKD patients. There was significant fall in serum calcium levels with decrease in eGFR in CKD patients. There was no significant correlation between serum sodium levels and eGFR in CKD patients.